Validity of the powerline boat instrumentation system - Coker, J.; Hume, P.; Nolte, V. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The PowerLine Boat Instrumentation System3 is comprised of instrumented oarlocks capable of measuring pin forces in the direction of boat travel and oarlock angles. The aim of this study was to determine the reliability and validity of the force and angle data from the PowerLine Boat Instrumentation System in a laboratory setting. Data were collected with the sculling oarlocks affixed to a horizontally aligned, stabilised wing rigger. For force analysis, signals were collected at 50 Hz from both the PowerLine system and a 1 kN load cell4 during 10 repetitions at a rate of approximately 30 repetitions per minute. For angular analysis, whilst recording with PowerLine, oarlocks were repositioned for a minimum of two seconds at known angles in a random order using an inclinometer accurate to one tenth of a degree over a range of -80° to +60°, in 20° increments. Linear regression analysis through the origin was used to compare the PowerLine values with known values from the load cell and the inclinometer. Laboratory testing proved the force and angle sensors to be valid throughout the testing range (0 N to 554.8 + 20.4 N, and -80° to +60° respectively) when fully functioning. The PowerLine Boat Instrumentation System appears to be appropriate for measuring biomechanical variables in an elite sculling programme. On-water reliability testing is still required to fully evaluate their application in quantifying the effect of interventions made to technique or boat set-up.